2001
DOI: 10.1046/j.0021-8790.2001.00535.x
|View full text |Cite
|
Sign up to set email alerts
|

Age‐specific breeding probability in black brant: effects of population density

Abstract: Summary 1.We estimated age-specific probability of breeding for black brant ( Branta bernicla nigricans Lawrence) (hereafter brant) at the Tutakoke River Colony, Alaska, during a series of years in which local breeding density and juvenile mortality both increased. We use these analyses to examine demographic responses to increased population density. 2. Estimates of breeding probability were based on Kendall & Nichols (1995) fulllikelihood modification of Pollock's (1982) robust design applied to observations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
72
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 53 publications
0
72
3
Order By: Relevance
“…Density-dependent processes often interact with other variables including predation, harvest, and genetics, as well as density independent factors such as climate-those interactions can make density-related processes difficult to document (McCullough 1979(McCullough , 1990White and Bartmann 1997;Bowyer et al 1999;Aanes et al 2000). Density dependence has been investigated in birds (Sedinger et al 2001;Both and Visser 2003;Elmberg et al 2003), small mammals (Aars and Ims 2002), carnivorous mammals (Fryxell et al 1999;Macdonald et al 2002), and large, herbivorous mammals (McCullough 1979;Kie and White 1985;Bowyer et al 1999;Mysterud et al 2000;Saether et al 2002;Toigo et al 2002) with varying results, because most organisms exhibit both density-dependent and density-independent characteristics.…”
Section: Introductionmentioning
confidence: 98%
“…Density-dependent processes often interact with other variables including predation, harvest, and genetics, as well as density independent factors such as climate-those interactions can make density-related processes difficult to document (McCullough 1979(McCullough , 1990White and Bartmann 1997;Bowyer et al 1999;Aanes et al 2000). Density dependence has been investigated in birds (Sedinger et al 2001;Both and Visser 2003;Elmberg et al 2003), small mammals (Aars and Ims 2002), carnivorous mammals (Fryxell et al 1999;Macdonald et al 2002), and large, herbivorous mammals (McCullough 1979;Kie and White 1985;Bowyer et al 1999;Mysterud et al 2000;Saether et al 2002;Toigo et al 2002) with varying results, because most organisms exhibit both density-dependent and density-independent characteristics.…”
Section: Introductionmentioning
confidence: 98%
“…In addition to generating estimates of apparent U, the robust design provides estimates of temporary emigration (c), capture probability ( p), and recapture probability (c). Our goal was to generate reliable estimates of U, given potential variance associated with temporary emigration (Kendall et al 1997), which may have occurred if males did not breed in each year of the study (Sedinger et al 2001). In a previous analysis we found that male density during year t was the best predictor of c tþ1 , so we incorporated a structure of c using this density covariate for all models.…”
Section: Survival Analysismentioning
confidence: 99%
“…Such a threshold has been well documented in both mammal and reptile species (reviewed by Shine 2003, Bonenfant et al 2009). Despite breeding propensity being considered a key demographic parameter (Sedinger et al 2001), it is the least understood reproductive decision in avian species (Sedinger et al 2001, Reed et al 2004. This parameter has rarely been tested in birds because non-breeders are often entirely absent from the breeding grounds, making comparisons to breeding birds challenging (Chastel 1995), and individuals are difficult to both capture…”
mentioning
confidence: 99%